An exploratory study on kaizen muda and organisational sustainability: patients' perspective. (2016) - Chahal, Hardeep; ,
The purpose of this paper is to measure patients' perception towards kaizen muda tool in organisational sustainability. The study used mixed method approach for muda/waste identification, measurement and suggestions for controlling muda/waste in the hospital. The quantitative approach was used for measuring the patients' perception towards kaizen muda/waste and organisational sustainability while qualitative approach was used for gathering patients view points for controlling these wastes. The results revealed five types of mudas/waste namely, overproduction waste, defects, transportation waste, waiting time waste and motion waste present in the hospital environment. The findings suggest that by controlling this mudas/waste the hospital can improve its level of sustainability-economical, social and ecological. The present study provides a platform for further research to be conducted at a larger scale for the development and validation of the kaizen muda/waste and organisational sustainability scale for the healthcare sector.